Driving Performance Excellence: Insights from Retail Sector on Transformational Leadership and Knowledge Sharing Behavior - Rinawati, Rinawati; Sidharta, Iwan (Center of Research, STIE Pasundan, Bandung, Indonesia., 2024)
This research delves into the pivotal role of Knowledge-sharing behavior and Transformational Leadership in enhancing employee performance within the retail sector. By investigating the relationships between these key factors, the study aims to provide valuable insights for optimizing workforce effectiveness and driving organizational success. The research methodology involves a quantitative approach, with data collected through surveys from 96 retail sector employees in Bandung. Instruments validated by reputable researchers were utilized to measure transformative leadership, Knowledge-sharing behavior, and employee performance. Data quality was assessed using outer loading, AVE, Composite Reliability, and Cronbach's Alpha, followed by analysis through Partial Least Squares. The findings are expected to shed light on how fostering a culture of knowledge exchange and implementing transformative leadership practices can positively impact employee performance in the retail industry. Ultimately, this research seeks to offer practical recommendations for retail organizations looking to enhance operational efficiency, employee engagement, and overall performance in a competitive market environment.